Exploration of Integrated Mathematics Learning with Teaching Factory Learning for Vocational High School Pharmacy Students Based on Design Thinking - Utomo, Hary Nurprio Utomo; Utomo, Hary Nurprio; Muhtarom, Muhtarom; Dwijayanti, Ida (Jurnal Gantang, 2025)
There are still many vocational high school students who struggle with mathematics and need mathematics instruction that is more focused on what they need to support their vocational studies. This study aims to qualitatively and quantitatively explore emerging issues in mathematics learning using the design thinking method, which consists of 5 stages: empathize, define, ideate, prototype, and test. In this research exploration, only the first 3 stages were completed: empathize, define and ideate. The study population consisted of 10th-grade students majoring in pharmacy and mathematics teachers at SMK Al Manaar Muhammadiyah, SMK Amanah Husada, and SMK Media Farma, with 50 10th-grade student respondents and 6 teachers. Quantitative data were collected via a Google Forms questionnaire, while qualitative data were collected through interviews. The data were then analyzed from the empathy stage to the ideate stage, and it was found that students and teachers in mathematics learning need direct practice to support their vocational skills. Therefore, the researcher concludes that it is necessary to integrate mathematics learning into the vocational studies of SMK students, which can involve the active participation of both students and teachers in mathematics learning.